Pengaruh Work-Life Balance terhadap Kinerja Karyawan Universitas Global Jakarta - Rahmawati (Jurnal Administrasi Karya Dharma, 2024)
The purpose of this research is to determine the influence of Work-Life Balance on Employee Performance among Employee at Jakarta Global University and to assess the extent of its impact. This study aims to explore the impact of Work-Life Balance on employee performance in the context of Universitas Global Jakarta. The findings provide a comprehensive understanding of the relationship between work-life balance and individual performance levels within the university environment. This study makes a valuable contribution to the practical and theoretical understanding of the importance of Work-Life Balance in an academic context. Its implications can assist university management or similar institutions in designing policies that support this balance, with the hope of improving employee performance and satisfaction. The research sample consists of 113 individuals. Data were obtained through interviews and questionnaires. The model of analysis in this study using Structural Equation Model (SEM). While the tool in this study using SmartPLS 2.0 M3 program. The results of hypothesis testing and discussion show that Work-Life Balance positive influence significantly toward Employee Performance. This indicates that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, meaning that Work-Life Balance have significantly positive influences to Employee Performance of Jakarta Global University Employee.